Pediatric invasive disease due to Haemophilus influenzae serogroup A in Riyadh, Saudi Arabia: case series - Zailaie Roaa; Alawfi Abdulsalam; Ghazi Shahid; Baba Kamaldeen; Al Fawaz Tariq (Journal of Infection in Developing Countries)
We describe the first two cases of invasive disease caused by Haemophilus influenzae serotype A in Saudi Arabia. This is the first known reported invasive Haemophilus influenzae serotype A from Saudi Arabia. Case presentation: A ten-month-old and three-month-old male not known to have any past history of any medical illness and who had received H. influenzae type b (Hib) vaccine presented to our hospital mainly with fever of few days’ duration. A provisional diagnosis of meningitis with sepsis was made and laboratory tests were requested. The chest radiograph was normal. The laboratory results revealed leukocytosis, but leukopenia was noticed in the younger infant. Blood culture and cerebrospinal fluid specimens yielded a pure culture of Haemophilus influenzae and serotyping showed the isolates to be serogroup A. Both patients were started on vancomycin and third-generation cephalosporin. On receiving the blood culture result, vancomycin was stopped. Fever subsided after 48 hours, while in the second case, it continued for 12 days from the admission date. The repeat blood cultures were negative. Antibiotic therapy was given for 10 days for the first case with an unremarkable hospital course, while the second case was complicated by seizure and received a longer duration of antibiotics. Both infants were discharged home in good condition. Conclusions: Invasive non-typeable H. influenzae strains are emerging and there is a need for surveillance of this disease. This has implications in future vaccine development.